Teacher - Pedagogical Creativity and Developer Promoter - Riashchenko, Viktorija; Živitere, Marga Brigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Creative trends in the formation of professional and pedagogical culture of the teacher, including the creation, development and use of pedagogical innovations is a means of updating educational policy with regard to the training of highly qualified personnel . It is Therefore the development of pedagogical creativity is an important condition for successful education. Pedagogical creativity directly affects the development of the student. Furthermore, professional motivation is an important factor for the competitiveness of the institution. Higher vocational training is a fundamental component of an integrated system of continuing professional education in today's highly competitive job market. The process of developing professional motivation in modern conditions is not possible without the use of pedagogical creativity.